(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The purpose of this research is to explore Edmond Husserl’s critique of transcendental philosophy at Immanuel Kant. Husserl, on the basis of this critique, defined philosophy as an rigorous science, rejecting the Kantian vision of the function of philosophy while attempting in the same time to establish an innovative Transcendental philosophy based on completely new foundations In order to establish the objectivity of the subjects, based on their own effectiveness, but will prevent fundamental obstacles to Husserl from the formation of objectivity stems from its limitation on the beat of transcendental solipsism in the justification of the objective fact of the subjects within the consciousness.